Extracellular vesicles in neurodegenerative diseases: A systematic review - Raghav, Alok; Singh, Manish; Jeong, Goo-Bo; Giri, Richa; Agarwal, Saurabh; Kala, Sanjay; Gautam, Kirti Amresh (Frontiers in Molecular Neuroscience, 2022)
Extracellular vesicles (EVs) are known to have a significant role in the central nervous system (CNS) and neurodegenerative disease. PubMed, Scopus, ISI Web of Science, EMBASE, and Google Scholar were used to identify published articles about EV modifications (2012 to Feb 2022). 1435 published papers were identified among the searched articles, with 1128 non-duplicate publications identified. Following the screening of titles and abstracts, 214 publications were excluded; following the full-text screening of 93 published articles, another 33 publications were excluded. The remaining 60 studies were considered. The Kappa statistic of 0.868 indicated that the raters were highly reliable. Furthermore, the inter-reliability and intra-reliability coefficients were found to be.931 and.908, respectively, indicating strong reliability and consistency between the eligible studies identified by the raters. Twenty-seven relevant studies demonstrated the role of EVs as therapeutic and diagnostic biomarkers in neurodegenerative diseases. Nineteen and fourteen studies, respectively, found EVs to be pioneering in diagnostic and therapeutic roles. EVs, play an important role in the central nervous system (CNS), aiding in cell-to-cell communication and serving as a diagnostic marker and therapeutic target in a variety of neurodegenerative diseases. EVs are the home of several proteins (including -synuclein (-syn) and tau proteins), lipids, and genetic materials such as DNA and RNA. The presence of novel miRNAs in EVs suggests biomarkers for neurodegenerative disorders diagnosis and screening. Furthermore, EVs play an important role in the pathogenesis of such disorders. This systematic review will discuss the current state of EVs' role in neurological diseases, as well as some preclinical studies on EVs' therapeutic and diagnostic potential.